Targeting Tumor Associated Macrophages to Overcome Conventional Treatment Resistance in Glioblastoma - Grégoire, Hélène; Roncali, Loris; Rousseau, Audrey; Chérel, Michel; Delneste, Yves; Jeannin, Pascale; Hindré, François; Garcion, Emmanuel (Frontiers in Pharmacology, 2020)
Glioblastoma (GB) is the most common and devastating form of brain cancer. Despite conventional treatments, progression or recurrences are systematic. In recent years, immunotherapies have emerged as an effective treatment in a number of cancers, leaving the question of their usefulness also faced with the particular case of brain tumors. The challenge here is major not only because the brain is the seat of our consciousness but also because of its isolation by the blood-brain barrier and the presence of a unique micro-environment that constitutes the central nervous system (CNS) with very specific constituent or patrolling cells. Much of the microenvironment is made up of immune cells or inflammation. Among these, tumor-associated macrophages (TAM) are of significant interest as they are often involved in facilitating tumor progression as well as the development of resistance to standard therapies. In this review, the ubiquity of TAM in WBG will first be discussed. Next, the specific case of microglia resident in the brain will be discussed. In addition, the roles of TAM as accomplices in the progression of GB and resistance to treatment will be presented. Finally, clinical trials targeting TAM as a means of treating cancer will be discussed.